The impact of social transfers in Central and Eastern Europe - Alfio Cerami (Luxembourg Income Study (LIS), 2003)
This paper analyses the impact of social transfers in seven Central and Eastern European countries using 16 datasets provided by the Luxembourg Income Study (Czech Republic 1992, 1996; Estonia 2000; Hungary 1991, 1994, 1999; Poland 1986, 1992, 1995, 1999; Romania 1995, 1997, Slovakia 1992, 1996; Slovenia 1997, 1999). The principal objective is (a) to provide an overview of the development of social inequality in Central and Eastern Europe; and (b) to quantify the change of poverty rates among the total population and among targeted groups (unemployment compensation, means-tested and family benefits beneficiaries) before and after transfers. The results of this paper show that although the access to these benefits is no guarantee for leaving poverty, social transfers significantly improve the economic conditions of families in need. Without the existence of these types of provisions, Central and Eastern European societies would not only be more unequal societies, but would be also more atomised and disaggregated societies. In the long run, this might seriously damage further reforms or the democratisation process itself.
Keywords: 330; Öffentliche Sozialleistungen; Haushaltseinkommen; Armut; Osteuropa